الوحي: تعريفه، أنواعه، وكيفيته، وتتفنيد شبه الجاحدين له - الهويمل، تركي بن سعد بن فهيد بن قميش (جامعة الإمام محمد بن سعود الإسلامية, 2015)
يتكون البحث من مقدمة، وتمهيد، وثلاثة فصول، وخاتمة. المقدمة : وفيها بيان أهمية الموضوع، وأسباب اختياره، وخطة البحث، والمنهج المتبع في إنجازه، التمهيد : ويشتمل على مسألتين : المسألة الأولى : إمكانية وقوع الوحي، المسألة الثانية : حاجة البشر إلى الوحي. الفصل الأول : تعريف الوحي، وأدلة وقوعه، وفيه مبحثان : المبحث الأول : تعريف الوحي في اللغة والشرع، والمبحث الثاني : أدلة وقوع الوحي من الكتاب، والسنة، والعقل، والفصل الثاني : أنوع الوحي، وكيفيفته، وفيه ستة مباحث : المبحث الأول : أنواع والوحي بالمعنى اللغوي، والمبحث الثاني : أنواع الوحي بالمعنى الشرعي، ثم المبحث الثالث والرابع والخامس والسادس في كيفية وحي الله – عز وجل – إلى ملائكته وإلى جبريل عليهم السلام، وكيفية وحي الله عز وجل إلى رسله، وكيفية وحي الملك إلى الرسول صلى الله عليه وسلم، الفصل الثالث : شبه الجاحدين على الوحي وتفنيدها. ثم الخاتمة، وفيها أهم نتائج البحث، ثم الفهارس العامة للبحث.
The Research consists of an introduction, a preface, three chapters and a conclusion. The introduction shows the importance of the topic, reasons of selection, research proposal and the research methodology. The preface includes two issues which are the possibility of revelation and human need for revelation. The first Chapter includs the definition of revelation and evidence of its occurrence. It consists of two parts: the first part discusses the definition of revelation in language and Shari‘a, and the second part presents the evidence of revelation from Holy Quran, Sunnah and Reason. The second chapter, which consists of six parts, includes the types of revelation, and how it was done. The first part discusses the types of revelation in language, the second part discusses the types of revelation in Shari‘a, and then the third, fourth, fifth and sixth parts includes how Allah revealed to the Angles, Gabriel, and his messengers, as well as how the Angle revealed to messenger Muhammad, peace be upon him. The third chapter examins the arguments of the revelation deniers and refuted them. Then, the conclusion that includes the most important results of the research and the list of the research general references.
Keywords: العقيدة الإسلامية -- الوحي -- المباحث القرآنية -- درء الشبهات -- الملائكة -- الأنبياء والرسل